PENGARUH KUALITAS PELAYANAN, HARGA DAN KEPERCAYAAN PADA JASA PENGIRIMAN JNE TERHADAP LOYALITAS KONSUMEN ONLINE SHOPEE - Wahyuni, Ika; Pramitasari, Triska Dewi (Growth, 2022)
The statistical test of the regression results Y=7.023E-16+0.576X1+0.316X2+0.076X3+e showed that research data was collected for both the dependent variable (Y) and the independent variable (X1, X2, X3). The t-test is to know the magnitude of the influence of the Service Quality variable (X1) on Consumer Loyalty (Y) of 6,400. Meanwhile, the value in the 5% distribution ttable is 1.988, then tcount 6.400 > 1.988 t table meaning that the Service Quality variable has a partial effect on Consumer Loyalty in Economics Students at Abdurachman Saleh Situbondo University. Price Variable (X2) Against Consumer Loyalty (Y) of 2.871. Meanwhile, the value in the 5% distribution ttable is 1.988, then tcount 2.871 < ttable 1.988 meaning that the price variable has a simultaneous effect on Consumer Loyalty in Economics Students at Abdurachman Saleh University, Situbondo. The Trust Variable (X3) on Consumer Loyalty (Y) is 0.983. Meanwhile, the value in the 5% distribution t table is 1.988, then tcount 0.983 < 1.988 t table. Based on the dominant test of the Service Quality variable (X1) of 6.400, Price (X2) of -2.871 and Trust (X3) of 0.983, the conclusion is that the value of the Service Quality variable is greater than the other two independent variables, which is 6.400.